Smart Frequency Control using Coordinated RFB and TCPS based on Firefly Algorithm - Dwi Lastomo; Arif Musthofa; Herlambang Setiadi; Eddy Setyo Koenhardono; Muhammad Ruswandi Djalal (IAES Indonesia Section, 2018)
The frequency stability enhancement of a power system is proposed in this paper. To enhance the frequency stability, redox flow batteries (RFB) and the thyristor controlled phase shifter are used. Moreover, to get a better performance, the parameter of RFB and TCSC are optimized by the firefly algorithm (FA). Two area load frequency control plant is used as a test system. Time domain simulation is used to assess the performance of the proposed method (adding RFB and TCPS and optimized using FA). From the simulation results, it is found that by installing RFB and TCSC based on FA in the system, the frequency performance can be maintained above the nadir when perturbation emerges.